The reality of practicing educational competencies among physical education and sports teachers in secondary education - medjadi, Rabah (sports creativity, 2025)
This study aimed to determine the actual practice of teaching competencies among physical education teachers in secondary schools. The study was conducted in several secondary schools in the province of M'Sila, specifically on a sample of 12 teachers randomly selected from a total of 75 representing the original population, during the 2010/2011 academic year. Using the descriptive method, one of the most widely used approaches in social and psychological studies, and employing a teaching competency scale proposed by the researcher, the results of the study, after collecting data, showed the following: • The teaching competencies that physical education teachers should practice are: planning (preparation) competencies, implementation competencies, classroom management competencies, and assessment competencies. • The level of practice of teaching competencies by the teachers is average, according to their own perspective.